World history to 1800 - Spielvogel, Jackson A. (West Educational Publishing, 1999)
This is a world history text that covers world history though the year 1800. It presents each major civilization-such as China, India, and Europe-and provides points of comparison between and among these civilizations. It emphasizes breadth and accessibility and contains a wealth of primary source documents, beautiful full-color maps, and interesting teaching and learning supplements to help students appreciate the complexity of the topic while enjoying its application to their lives.